Social norms and fertility intentions: Evidence from China - Yu, Xiao; Liang, Jianing (Frontiers in Psychology, 2022)
China’s low fertility rates are a major concern across all sectors of society. Fertility is a major issue related to economy, society and family development. Based on social norms theory, this paper explores the influence of social norms on individuals’ fertility intentions from two perspectives: spatial proximity and social proximity. Using data from the China Family Panel Studies, we found that individual’s fertility intentions were influenced by social norms; both neighborhood social norms and group social norms had significant effects. The role of social norms in shaping individual fertility intentions varied by gender, hukou, and life course; specifically, men, rural residents, and married individuals were more significantly influenced by social norms. This study improves the theoretical framework of fertility decision making by arguing that in addition to macro and individual factors, social norms have a very important influence on fertility intentions. Our findings suggest that reshaping social norms regarding fertility is essential to enhance fertility rates in China.